The effect of Morus alba leaves extract and powder on resistin levels and liver transaminase enzymes activities in diabetes - Salemi, Z; Barzin Tond, S; Fallah, S; Shojaii, A; Seifi, M (Cellular and Molecular Biology, 2016)
The current study was designed to investigate the changes of the resistin, aspartate aminotransferase (AST), alanine aminotransferase (ALT) levels of diabetic rats after treatment with Morus alba leaves flavonoid extract (MLE) and Morus alba leaves powder (MLP). Thirty male wistar rats in five groups including control and diabetic groups were included. Diabetic groups consisted of diabetic control, sham and treated group with MLE and MLP. Type 2 diabetes was induced in rats by administration of streptozotocin (STZ) and nicotinamide. The serum concentrations of resistin and insulin in the study groups were identified by ELISA. ALT and AST activities were assayed by spectrophotometer. For the first time, it was shown that the uptake of MLE and MLP by diabetic rats could significantly decrease the serum fasting blood sugar (FBS), resistin levels and enzymes activity of ALT and AST and increases the concentration of serum insulin significantly (P<0.05). in comparison with the sham group and diabetic control. The results showed that there was no significant difference between the anti-diabetic and inflammatory properties of MLE and MLP. In this study, the possible protective effect of MLE and MLP administration was evaluated against destructive effect of STZ on liver and pancreas function in diabetic rats. The results showed that these effects may play an important role in the regulating of adipokines secretion such as resistin and insulin secretion which are involved in the control of diabetes and obesity. MLE and MLP treatment could be useful agents in combination with other therapies in diabetes improvement.